Building Successful Multicultural Special Education Programs Through Innovative Leadership - Festus E. Obiakor; Floyd D. Beachum; Darrell Williams; Carlos R. McCray (Educational Considerations, 2006)
Across America’s schools, administrators are faced with various educational challenges.
Keywords: Successful; programs; multicultural; students; special needs